Experiencing depersonalised bullying: a study of Indian call-centre agents. (1st July 2009) - ,; ,
Abstract : This article uses the concept of depersonalized bullying to explain the way in which call-centre agents employed in international call centres in Mumbai and Bangalore, India experience their work as an oppressive regime. The characteristics of this bullying regime can be attributed to the service level agreement between employers and clients which determines organisational practices. Call-centre agents' professional identities and material gains facilitate their acceptance of their tough work conditions, causing them to participate in their own oppression. As well as clarifying the concept of depersonalised bullying, the article highlights the critical role of capitalist labour relations in workplace bullying, allowing for a contextualised and politicised understanding to emerge.